2009
DOI: 10.1111/j.1467-8535.2008.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mobile learning on students' learning behaviours and performance: Report from a large blended classroom

Abstract: Minjuan Wang is an associate professor of Educational Technology at San Diego State University. Her research specialties focus on the sociocultural facets of online learning, mobile learning and technological interventions in language education. She has published peer-reviewed articles in Educational Technology Research and Development, Computers and Education, Educational Media International, TechTrends, and the British Journal of Educational Technology. She has also published book chapters on engaged learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
202
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(219 citation statements)
references
References 8 publications
6
202
0
11
Order By: Relevance
“…Similarly, the student decides the study time (Garnham & Kaleta, 2002;Smyth, Houghton, Cooney, & Casey, 2012;Gómez & Duart, 2012;Mitchell & Honore, 2007). Studies show that students who pursue courses through the hybrid learning are better motivated and pay more attention during the study process (Sharpe, Benfield, Roberts, & Francis, 2006;Woltering, Herrler, Spitzer, & Spreckelsen, 2009;Donnelly, 2010;Wang, Shen, Novak, & Pan, 2009;Martinez-Caro & Campuzano-Bolarin, 2011). Professors argue that hybrid courses develop critical thinking skills in students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, the student decides the study time (Garnham & Kaleta, 2002;Smyth, Houghton, Cooney, & Casey, 2012;Gómez & Duart, 2012;Mitchell & Honore, 2007). Studies show that students who pursue courses through the hybrid learning are better motivated and pay more attention during the study process (Sharpe, Benfield, Roberts, & Francis, 2006;Woltering, Herrler, Spitzer, & Spreckelsen, 2009;Donnelly, 2010;Wang, Shen, Novak, & Pan, 2009;Martinez-Caro & Campuzano-Bolarin, 2011). Professors argue that hybrid courses develop critical thinking skills in students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…‫ميزات‬ ‫من‬ ‫التربوي‬ ‫األدب‬ ‫إليه‬ ‫أشار‬ ‫ولما‬ ‫التعلم‬ ‫من‬ ‫النوع‬ ‫لهذا‬ ( e.g., Singh, 2010;Lei, 2010;Donnelly, 2010;Wang et al, 2009;Voci, & Young, 2001 ،) ‫تقييم‬ ‫ضرورة‬ ‫إلى‬ ‫باإلضافة‬ ‫والمستحدثات‬ ‫الحديثة‬ ‫التقنيات‬ ‫مساهمة‬ ‫مدى‬ ‫عند‬ ‫وخاصة‬ ‫الطلبة،‬ ‫تعلم‬ ‫في‬ ‫التكنولوجية‬ …”
unclassified
“…Other studies that are related to establishing the mobile learning foundation focused on students' perceptions and attitudes in using this sort of technology. Findings from these researches revealed that the integration of mobile-learning into classrooms generated strong positive interests among students [18], [19]& [20]. Furthermore, there were studies that indicated students really enjoyed learning via mobile devices [21]& [22] and they believed that they were competent and at ease when using the mobile devices in performing learning assignments [23]& [24].…”
Section: Learning Via Mobile Technologymentioning
confidence: 99%